Upregulation of Circular RNA CircNFIB Attenuates Cardiac Fibrosis by Sponging miR-433 - Zhu, Yujiao; Pan, Wen; Yang, Tingting; Meng, Xiangmin; Jiang, Zheyi; Tao, Lichan; Wang, Lijun (Frontiers in Genetics, 2019)
Cardiac fibrosis is the pathological consequence of fibroblast proliferation and fibroblast-to-myofibroblast transition. As a new class of endogenous noncoding RNAs, circular RNAs (circRNAs) have been identified in many cardiovascular diseases including fibrosis, generally acting as microRNA (miRNA) sponges. Here, we report that the expression of circRNA-circNFIB was decreased in mice post-myocardial infarction heart samples, as well as in primary adult cardiac fibroblasts treated by TGF-β. Forced expression of circNFIB decreased cell proliferation both in NIH/3T3 cells and primary adult fibroblasts as evidenced by EdU incorporation. Conversely, inhibition of circNFIB promoted adult fibroblasts proliferation. Furthermore, circNFIB was identified as a miR-433 endogenous sponge. Overexpression of circNFIB could attenuate pro-proliferative effects induced by miR-433 mimic while inhibition of circNFIB exhibited opposite results. Finally, upregulation of circNFIB also reversed the expression levels of target genes and downstream signaling pathways of miR-433. In conclusion, circNFIB is critical for protection against cardiac fibrosis. The circNFIB-miR-433 axis may represent a novel therapeutic approach for treatment of fibrotic diseases.